Pengaruh Waktu dan Jarak Tempuh ke Gerbang Tol terhadap Harga Tanah - Satrio Muhammad Alif; Anisa Rahma Dhanty (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2022)
One of the reasons for the construction of the Trans Sumatra toll road is the increase in traffic in Bandar Lampung. Travel time and distance to the three toll can affect land prices. The purpose of this study is to obtain the effect of time and distance to three toll gates on land prices. This study uses 11,904 travel time data from Google Maps with details of 124 villages to three toll roads for 8 weeks, with one week there are 2 data on weekdays and 2 data on weekends. The villages point is used to represent Bandar Lampung and is obtained from the midpoint of the kelurahan. The method to get the effect on land prices is multiple linear regression with least squares technique. The results are linearly interpolated to get the time area and distance traveled to the three toll gates. The farthest distance is the distance to the Natar toll gate and the closest distance is to the ITERA toll gate. The ITERA toll gate is the toll gate that most affects land prices in the city of Bandar Lampung, but the distance to the city center is the most influential factor in determining land prices.